2021
DOI: 10.3390/ijms22052562
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Prognostic Impact of the KIT D816V Transcriptional Activity in Advanced Systemic Mastocytosis

Abstract: In systemic mastocytosis (SM), qualitative and serial quantitative assessment of the KIT D816V mutation is of diagnostic and prognostic relevance. We investigated peripheral blood and bone marrow samples of 161 patients (indolent SM (ISM), n = 40; advanced SM, AdvSM, n = 121) at referral and during follow-up for the KIT D816V variant allele frequency (VAF) at the DNA-level and the KIT D816V expressed allele burden (EAB) at the RNA-level. A round robin test with four participating laboratories revealed an excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The reliability and validity of our registry data has been demonstrated individually 6,7,9,21-25,27,37-39 and also in relation to several projects of the ECNM. 5,6,40-45 For the current analyses, salient strengths include (1) a comprehensive data set of clinical and molecular parameters from baseline and on-treatment from a high number of patients of whom > 70% were repeatedly seen at the same institution, (2) evaluation of almost all BM biopsies by ECNM reference pathologists, 9,30 and (3) the use of widely acknowledged statistical methodologies through propensity score analyses as an optimal approach for comparing outcomes across cohorts with balanced distributions and the best possible approximation of a randomized trial.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The reliability and validity of our registry data has been demonstrated individually 6,7,9,21-25,27,37-39 and also in relation to several projects of the ECNM. 5,6,40-45 For the current analyses, salient strengths include (1) a comprehensive data set of clinical and molecular parameters from baseline and on-treatment from a high number of patients of whom > 70% were repeatedly seen at the same institution, (2) evaluation of almost all BM biopsies by ECNM reference pathologists, 9,30 and (3) the use of widely acknowledged statistical methodologies through propensity score analyses as an optimal approach for comparing outcomes across cohorts with balanced distributions and the best possible approximation of a randomized trial.…”
Section: Discussionmentioning
confidence: 57%
“…17-20 KIT D816V independent somatic mutations, for example, in SRSF2 , ASXL1 , and RUNX1 ( S/A/R gene panel), and cytogenetic aberrations are frequently identified in AdvSM and confer an inferior response to treatment, more rapid disease progression, for example, into secondary MCL or secondary AML, and reduced overall survival (OS). 6,21-27…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic mastocytosis is a rare myeloproliferative neoplasm in which malignant mast cells infiltrate bone marrow and other extracutaneous tissues such as liver, spleen, and peripheral blood. More than 90% of adult patients with this disease present a gain-of-function mutation in exon 17 within the c- kit gene, particularly KIT D816V, a missense mutation in which aspartic acid is substituted by valine in codon 816 [ 13 , 91 ]. Through kinase assays, it has been shown that the D816V mutant can autoactivate 586-fold faster than native c-KIT [ 79 ], which explains the adverse prognostic impact of the c- kit mutation in this hot spot in patients with systemic mastocytosis [ 91 ].…”
Section: C-kit and Cancermentioning
confidence: 99%
“…More than 90% of adult patients with this disease present a gain-of-function mutation in exon 17 within the c- kit gene, particularly KIT D816V, a missense mutation in which aspartic acid is substituted by valine in codon 816 [ 13 , 91 ]. Through kinase assays, it has been shown that the D816V mutant can autoactivate 586-fold faster than native c-KIT [ 79 ], which explains the adverse prognostic impact of the c- kit mutation in this hot spot in patients with systemic mastocytosis [ 91 ]. The D816V mutation is also present in children with systemic mastocytosis but with a lower frequency (42%).…”
Section: C-kit and Cancermentioning
confidence: 99%